2020
DOI: 10.1101/2020.07.24.220780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of IgG Subclass in Antibody-Mediated Protection against Carbapenem-ResistantKlebsiella pneumoniae

Abstract: Monoclonal antibodies (Abs) have the potential to assist in the battle against multidrug-resistant bacteria such as Carbapenem-Resistant Klebsiella pneumoniae (CR-Kp). However, the characteristics by which these Abs function, such as the role of antibody subclass, must be determined before such modalities can be carried from the bench to the bedside. We performed a subclass switch on anti-capsular monoclonal murine IgG3 (mIgG3) hybridomas and identified and purified a murine IgG1 (mIgG1) hybridoma line through… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Kobayashi et al [95] found that there is limited neutrophil phagocytosis of ST258 clinical isolates, a phenotype conferred largely by the CPS. Subsequent work by Diago-Navarro et al [96], Kobayashi et al [97], and Motley et al [98] demonstrated that phagocytosis and killing of ST258 are enhanced significantly by CPS-specific antibodies [96][97][98]. These results provide strong support to the idea that the CPS of ST258 can be used as vaccine antigen and/or target.…”
Section: Phagocytes and Host Defense Against K Pneumoniaementioning
confidence: 76%
See 1 more Smart Citation
“…Kobayashi et al [95] found that there is limited neutrophil phagocytosis of ST258 clinical isolates, a phenotype conferred largely by the CPS. Subsequent work by Diago-Navarro et al [96], Kobayashi et al [97], and Motley et al [98] demonstrated that phagocytosis and killing of ST258 are enhanced significantly by CPS-specific antibodies [96][97][98]. These results provide strong support to the idea that the CPS of ST258 can be used as vaccine antigen and/or target.…”
Section: Phagocytes and Host Defense Against K Pneumoniaementioning
confidence: 76%
“…For example, designing antibodies that target only K. pneumoniae epitopes could potentially eliminate the pathogen and spare beneficial bacteria that constitute a healthy microbiome [154]. In vitro and in vivo studies indicate the use of specific antibodies dramatically increases uptake and killing of K. pneumoniae by immune cells, which consequently leads to improved recovery and increased survival in animal infection models [96][97][98]151]. Diago-Navarro et al [155] generated mAbs specific for the CPS of an ST23 hvKp strain (K1 capsule serotype) and then demonstrated the ability of these mAbs to protect against bacterial dissemination in a mouse infection model.…”
Section: Vaccines and Novel Therapeutic Approachesmentioning
confidence: 99%